Temporal variations of the ionospheric disturbances due to the seasonal variability over Turkey using IONOLAB-FFT algorithm - Karatay, Secil (Elsevier BV, 2020)
The ionosphere is exposed to forcing from below due to gravitational, geomagnetic and seismic activities, and above due to solar wind. These forces cause some medium and large scale irregularities and disturbances into the upper atmosphere and ionosphere. Some of these disturbances occur in the form of wave-like oscillations in the ionosphere which propagate at a certain frequency, duration and velocity. These disturbances can be detected by monitoring the ionosphere using Total Electron Content obtained from Global Positioning System (GPS-TEC). In this study, the temporal analysis of these disturbances due to the seasonal variability is carried out for a mid-latitude GPS network using Ionosphere Research Laboratory TEC (IONOLAB-TEC) over Turkey. The IONOLAB Fast Fourier Transform (FFT) algorithm is applied to GPS-TEC obtained from nine Turkish National Permanent GPS Network (TNPGN) active stations in Turkey for December (winter solstice), March (spring equinox), June (summer solstice), September (autumn equinox) months in 2010 (low solar activity), 2011 and 2012 (moderate solar activity). It is observed that the highest frequency accumulates around 0.2 mHz at morning and afternoon hours while it accumulates around 0.1 mHz at noon and night hours. The frequency increases from solar quiet year 2010 to solar quiet active year 2012. In all years, it is observed that most frequencies are grouped at higher frequencies for the equinox months. The lower frequencies are observed for the solstice months for all time intervals. The largest numbers of the durations accumulate around 100 min (1.66 h) for morning hours, 200 min (3.33 h) for noon hours, 200 min (3.33 h) for afternoon hours and 150 min (2.5 h) for night hours. After sunrise and sunset, the durations of the disturbances are shorter than those observed for noon and afternoon times. The duration shortens from solar quiet year 2010 to solar quiet active year 2012. The durations for equinox months are shorter than those for the solstice months.
Keywords: Total electron content; QB275-343; QC801-809; Global Positioning System; Geophysics. Cosmic physics; Ionosphere; IONOLAB-FFT; Geodesy; 13. Climate action